Carbon and nitrogen management for climate-resilient agriculture: Toward the 4p1000 target and sustainable development goals - J.K. Ladha; Debashis Chakraborty; Beverley Henry; Budiman Minasny (Soil Advances)
Carbon (C) and nitrogen (N) are crucial elements for supporting life on Earth, and are involved in two vital biological processes, namely photosynthesis and N fixation. While both elements are essential for food security, they also contribute to emissions of greenhouse gases (GHGs), namely CO2, N2O and CH4. Most studies on soil C sequestration focus on C, but N is also a critical factor influencing both C sequestration and GHG emissions. This brief review explores a range of crop and grassland management practices, including no-till, cover cropping, biochar application, precision nutrient management, and agroforestry, with a focus on co-optimizing SOC sequestration and N efficiency. Global studies indicate that no-tillage practices can significantly enhance C sequestration and achieve notable reductions in GHG emissions compared to conventional practices. Emerging technologies like nano-fertilizers, nitrification inhibitors, and deep-rooted crop varieties are discussed with their contextual relevance. The role of C crediting is discussed, and its co-benefits are assessed in incentivizing sustainable practices. To meet the goals of Sustainable Development (SDGs) and the 4p1000 Initiative, we suggest C and N management be tailored to local settings, and follow a whole-system approach, ensuring that farmers and local communities are involved in decision-making. Building climate-resilient farming systems will depend on connecting environmental benefits with financial support and strong policies that help farmers adopt and sustain these practices.